Question

since the sum of the zeroes of the quadratic polynomial ( (a+1) x^{2}+(2 a+3) x+(3 a+4) ) is -1
( therefore frac{-(2 a+3)}{a+1}=-1 )
[
left[because text { Sum of zeroes }=frac{-(text { Coefficient of } mathbf{x})}{text { coefficient of } mathbf{x}^{2}}right]
]
( Rightarrow a+1=2 a+3 Rightarrow a=-2 )
Now, product of zeroes ( =frac{3 a+4}{a+1}=frac{3(-2)+4}{-2+1}=2 )
( left[because text { Product of zeroes }=frac{text { Constant term }}{text { Coefficient of } mathbf{x}^{2}}right] )

# Given that the sum of the zeroes of the polynomial (a +1)x2+(2a +3)x+ (3a + 4) is -1. Find the product of its zeroes.

Solution